Analysis of Internal Control of Fixed Assets at the Department of Environment and Forestry of Sumedang Regency - Triadi Ramadani; Shofia Annisa R; Fanji Farman (Journal of Business, Accounting and Finance, 2021)
This study aims to determine the application of internal control of fixed assets as well as to find out documents and records regarding procedures for control of fixed assets implemented by the Department of Environment and Forestry of Sumedang Regency. This type of research is descriptive and data sources used in this study are primary and secondary data. Descriptive analysis method with a qualitative approach. The results showed that the Department of Environment and Forestry of Sumedang Regency. has implemented effective internal control of fixed assets, by carrying out supervision and segregation of duties of each relevant section, starting from procurement, acquisition, utilization, maintenance and depreciation of fixed assets owned by SKPD. This means that if internal control is properly implemented and implemented, it will be able to guarantee the security of organizational assets and their availability are used in accordance with agreed procedures, thus minimizing misuse or violations of fixed assets that may occur.